PENGARUH PENDAPATAN ASLI DAERAH, BELANJA MODAL, DAN UKURAN LEGISLATIF TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH - Mufid Khairi Huwaidi, - (2022)
This study aims to test and prove the validity of the relationship between local government financial performance through local revenue, capital expenditure, and legislative measures. This study uses the population of district/city governments throughout Indonesia in 2020. The hypothesis analysis technique for this research is multiple linear regression with STATA version 14. This research uses a saturated sample of 508 local governments throughout Indonesia. The results show that local government revenue has a positive significant effect on local government financial performance, capital expenditures have a positive effect on local government financial performance, and legislative size has a negative significant effect on local government financial performance. The contribution of this research to local government is to be able to use other variables in further research, to be able to develop the potential of existing sources of revenue and to use consistent financial reporting standards every year.This study aims to test and prove the validity of the relationship between local government financial performance through local revenue, capital expenditure, and legislative measures. This study uses the population of district/city governments throughout Indonesia in 2020. The hypothesis analysis technique for this research is multiple linear regression with STATA version 14. This research uses a saturated sample of 508 local governments throughout Indonesia. The results show that local government revenue has a positive significant effect on local government financial performance, capital expenditures have a positive effect on local government financial performance, and legislative size has a negative significant effect on local government financial performance. The contribution of this research to local government is to be able to use other variables in further research, to be able to develop the potential of existing sources of revenue and to use consistent financial reporting standards every year.